Application of geomorphometric characteristics to prioritize watersheds for soil and water conservation practices in the Lake Tana Basin, Ethiopia - Bogale, A. G.; Adem, Anwar A.; Mekuria, Wolde; Steenhuis, T. S. (Informa UK Limited, 2023)
This study employed geomorphometric analysis to characterize the four major watersheds (Gilgel Abay, Gumara, Rib, and Megech) of Lake Tana sub-basin, Ethiopia, and prioritize the watersheds for the implementation of SWC practices using GIS and remote sensing techniques. Also, the study analyzed streamflow and sediment data recorded at the outlets of each watershed to associate the geomorphometric prioritization result with recordings of the watersheds. Geomorphometric analysis results indicated that the Rib watershed is the most susceptible watershed for soil erosion and should be prioritized for the implementation of SWC practices. The analysis of streamflow and suspended sediment concentration suggest that the Rib watershed had the second maximum sediment yield (14.3 t ha−1 yr−1) compared to the other three watersheds. This is because of the low streamflow response of the watershed compared with the Gumara watershed which had the highest sediment yield (18.9 t ha−1 yr−1).